THE EFFECT OF PERSONALTY AND INCOME ON MATERIALISM AND IT IMPACT ON SMARTPHONE COMPULSIVE BUYING (CASE STUDY FOR STUDENT OF MAGISTER MANAGEMENT POSTGRADUATE PROGRAM SYIAH KUALA UNIVERSITY BANDA ACEH) - Fata, Khairul; Hidayat, Fahmi (JURNAL KEBANGSAAN, 2015)
Abstract: This study aims to determine the effect of personalty and income on materialism and it impact on smartphone compulsive buying for student of Magister Management Postgraduate Program Syiah Kuala University. The sample of the study are 205 student taken by purposive sampling. Data gathering is done by questionnaire, and then the data were analyzed by path analysis. The study found that personality and income have significant effect on materialism. The two of exogenous variable, the personality has more dominantly effect on materialism than the income. The personality and income also effect on compulsive buying. The personality has more dominantly effect on compulsive buying than the income. The materialism as intervening variable increase the effect of personality on compulsive buying, but it decrease the effect of income on compulsive buying. Keywords : Compulsive Buying, Materialism, Personality and Income. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kepribadian dan pendapatan terhadap materialisme serta dampaknya pada pembelian kompulsif smartphone dikalangan mahasiswa program studi magister manajemen PPS-Unsyiah. Sampel penelitian sebanyak 205 orang mahasiswa yang diambil secara purposive sampling. Pengumpulan data menggunakan kuesioner dan selanjutnya data dianalisis dengan menggunakan peralatan statistik path analysis. Penelitian menemukan bahwa kepribadian dan pendapatan berpengaruh terhadap materialisme. Di antara kedua variabel eksogen tersebut, kepribadian memiliki pengaruh lebih dominan terhadap materialisme bila dibandingkan dengan pendapatan. Kepribadian dan pendapatan juga berpengaruh terhadap pembelian kompulsif. Kepribadian juga memiliki pengaruh lebih dominan terhadap pembelian kompulsif bila dibandingkan dengan pendapatan. Materialisme sebagai variabel perantara memperkuat pengaruh kepribadian terhadap pembelian kompulsif, tetapi memperlemah pengaruh pendapatan terhadap pembelian kompulsif. Kata kunci : Pembelian Kompulsif, Materialisme, Kepribadian, dan Pendapatan